Ecopreneurship Business Model of Nusa Dua Hotels Resort Area - Ratih Pertiwi, Putu; Rahyuda, Irma (Udayana Journal of Social Sciences and Humanities, 2017)
The purpose of this research is to examine the ecopreneurship business model applied by star hotels in Nusa Dua Resort integrating environmental elements into tourism business. Related to the concept of sustainable tourism development that emphasizes the development of eco-tourism and efforts to achieve the prospective ideal conditions. To discover it, the necessary data from several five star hotels that linked to international chains in Nusa Dua Resort area used as samples. Analyzed using descriptive qualitative analysis technique where the elements of ISO 14001 are used as the indicators, and guidelines for the interview and questionnaires. The data that has been obtained, processed and extracted, into some graphs and tables, and described as a basis for conclusions of ecopreneurship business model applied by star hotels in Nusa Dua Resort. As the result, this research shows that the ecopreneurship business model applied by star hotels in Nusa Dua Resort in integrating the environmental elements into tourism business has 4 phases. Such as P-D-C-A where Plan adapted into environmental management system planning, Do adapted into implementation of environmental labeling and recycling, Check adapted into an environmental audit examination and evaluation of environmental performance, and Action adapted into action on regular management review.